THE MORRORCAN ELITE IN AL MAQREEZI’S BOOK “DURAR AL- UQUD AL- FARIDA”(845 A.H. / 1442 A.D.) - Abush, Farhad Haji (Journal of Duhok University, 2018)
This research aims at highlightening the information provided by Al-Maqreezi on Moroccan elite particularly the political, religious and scientific elite through his book “Durar Al- Uqud Al-Farida fi Trajum Al-Mufeeda. “Al-Maqreezi is regarded as one of the pioneers of writing history in Egypt during the Mamluki era. He was characterized by the abundance of production and by his great accuracy in mentioning his subjects . In this book he mentions the biographies of great figures of men and women of his age. He mentions in this book those who died after his birth in (766 A.H/1364 A.D.) and lived till about his death in (845 A.H. / 1442 A.D.). This book contains about 1473 biographies. The Moroccan eminent persons constitute 80% of these biographies (5.431%). In this book Al- Maqreezi provides good and unique information on the Moroccans in North-west Africa ,Syria ,Egypt and Hejaz during the Mamluki era. The research is divided into two sections in addition to the introduction and conclusions .The first section is devoted to Al- Maqreczi’s life and his book entitled ‘’ Durar AL-Farida’’, whereas the second section focuses on the Moroccans whom he deals with in that book where he talks about many Tunisian , Algerian and Moroccan eminent persons ,on the one hand ,and about political , administrative , religious and scientific figures , on the other hand . Al-Maqreezi allocates a lot of pages of that book to the Moroccan sultans , kings and princes and their biographies .He also writes the biographies of many Moroccan jurists and scholars who were distinguished in the various teaching and religious aspects in Syria , Egypt and Hejaz during the Mumluki era (648-923 A.H/1250-1517 A.D.).